Cephalaria kurdistanica (Caprifoliaceae), a new species from Kurdistan, west of Iran - Maroofi, Hosein; Tabad, Mohammad Aref; Rastegar, Azad (Phytotaxa, 2020)
A new species, Cephalaria kurdistanica, from Chehel-Cheshmeh mountain, west of Iran, is here described and illustrated. The new species is morphologically related to C. microcephala Boiss., C. procera Fisch. & Avé-Lall., and C. kotschyi Boiss. & Hohen., but it differs in chiefly stem size, size and shape of capitula, the number of phyllaries, shape of upper part of phyllaries, calyx shape and indumentum, and size of bristles of receptacle. As well as detailed description, distribution map, conservation status and ecology of the new species are given.